Economics of Fertilizer Use for Oat Forage Production in W. Rajasthan - Bhati, G N; Vyas, D L (Annals of Arid Zone, 2016)
Economic evaluation of field trials (1973-76) on oat forage production in relation to varying levels of N application was done. Statistical analysis of green fodder yield data was done for selection of 'best fit' economic optima for N use and revenue cost relationship. The study amply demonstrated that oat forage production at 100 kg N application yielded highest income per hectare with given factor-product price relationship under irrigated conditions in western Rajasthan.